Avaliação da disponibilidade de aceleradores lineares e os tratamentos realizados na radioterapia no Brasil - Oliveira, Letícia Del Conte de [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Radiotherapy is one of the most used treatments against cancer. It is a treatment that does not qualify if it uses ionizing radiation to reach the place where the tumor exists, being responsible for destroying or preventing the growth of tumor cells. In radiotherapy, there are some planning techniques that efficiently fight the tumor, these techniques are common, such as: Conventional Radiotherapy (2D), Conformed or Three-dimensional Radiotherapy (3D), Radiotherapy with beam intensity modulation (IMRT) and Modulated Volumetric Arc Therapy (VMAT) and are cited in this study. The objective of this study was to update the number of linear accelerators in Brazil for performing Radiotherapy in 2021 and to analyze the most used planning techniques among hospitals. Based on the results obtained from the form for physical services on radiotherapy services in Brazil, we observed that we currently have 266 radiotherapy services with 404 linear accelerators, and it was observed that the most offered technique is three- dimensional (3D) radiotherapy and the technique of more technology called Modulated Volumetric Arc Therapy (VMAT) is little used in Brazil, with São Paulo being the state that offers the most. Among the numbers of linear accelerators, we noticed that most radiotherapy services are concentrated in the southeast and south of the country, with this it was noticed that the northern region has little availability of accelerators, being the region that has two states without radiotherapy service.

A radioterapia é um dos tratamentos mais utilizados contra o câncer. É um tratamento no qual se utilizam radiações ionizantes para atingir o local onde existe o tumor, sendo responsável por destruir ou impedir o crescimento das células tumorais. Na radioterapia existem algumas técnicas de planejamentos que combatem de forma eficiente o tumor, essas técnicas são conhecidas como: Radioterapia Convencional (2D), Radioterapia Conformada ou Tridimensional (3D), Radioterapia com Modulação da intensidade do feixe (IMRT) e Arcoterapia Volumétrica Modulada (VMAT) e são citadas no presente estudo.O objetivo desse trabalho foi atualizar a quantidade de aceleradores lineares no Brasil para a realização da Radioterapia no ano de 2021 e analisar as técnicas de planejamento mais utilizadas entre os hospitais. Com base nos resultados obtidos através do formulário aplicado aos físicos sobre os serviços de radioterapia no Brasil, observamos que atualmente temos 266 serviços de radioterapia com 404 aceleradores lineares, e foi observado que a técnica mais oferecida é a radioterapia tridimensional (3D) e a técnica de mais tecnologia chamada de Arcoterapia Volumétrica Modulada (VMAT) é pouco utilizada no Brasil, sendo São Paulo o estado que mais oferece. Dentre os números de aceleradores lineares, percebemos que a maioria dos serviços de radioterapia se concentram na região sudeste e sul do país, com isso foi notado que a região norte apresenta pouca disponibilidade de aceleradores, sendo a região que apresenta dois estados sem serviço de radioterapia.
Assessment of the availability of linear accelerators and treatments performed in radiotherapy in Brazil
Keywords: Radiotherapy; Linear Accelerator; Quantification of linear accelerators; Treatments; Radioterapia; Acelerador Linear; Quantificação de aceleradores lineares; Tratamentos